Modeling of photo-conversion efficiency for hydrogenated amorphous Si p-i-n structures - Sachenko, A.V.; Sokolovskyi, I.O.; Kazakevitch, A.; Shkrebtii, A.I.; Gaspari, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
An analytical formalism to optimize the photoconversion efficiency η of
hydrogenated amorphous silicon-based (a-Si:H) solar cells has been developed. This
model allows firstly the optimization of a p⁺
-i-n sandwich in terms of carrier mobilities,
thickness of the layers, doping levels, and others. Second, the geometry of grid fingers
that conduct the photocurrent to the bus bars and ITO/SiO₂ layers has been optimized,
and the effect of non-zero incidence angles of Sun’s light has been included as well. The
optimization method has been applied to typical a-Si:H solar cells. The codes allow the
optimization of amorphous Si based solar cells in a wide range of parameters and are
available on the e-mail request.